Motivation towards dual career of European student-athletes - Lupo, C.; Guidotti, F.; Goncalves, C. E.; Moreira, L.; Doupona Topic, M.; Bellardini, H.; Tonkonogi, M.; Colin, A.; Capranica, L. (European Journal of Sport Science, 2015)
The present study aimed to investigate motivations for the dual career of European student-athletes living in countries providing different educational services for elite athletes: State-centric regulation-State as sponsor/facilitator (State), National Sporting Federations/Institutes as intermediary (Federation) and Laisser Faire, no formal structures (No Structure). Therefore, the European Student-athletes' Motivation towards Sports and Academics Questionnaire (SAMSAQ-EU) was administered to 524 European student-athletes. Exploratory Factor Analysis, and Confirmatory Factor Analysis were applied to test the factor structure, and the reliability and validity of the SAMSAQ-EU, respectively. A multivariate approach was applied to verify subgroup effects (P = 0.05) according to gender (i.e., female and male), age (i.e., =24 years, >24 years), type of sport (i.e., individual sport and team sport) and competition level (i.e., national and international). Insufficient confirmatory indexes were reported for the whole European student-athlete group, whereas distinct three factor models [i.e., Student Athletic Motivation (SAM); Academic Motivation (AM); Career Athletic Motivation (CAM)] emerged, with acceptable reliability estimates, for State (SAM = 0.82; AM = 0.75; and CAM = 0.75), Federation (SAM = 0.82; AM = 0.66; and CAM = 0.87) and No Structure (SAM = 0.78; AM = 0.74; and CAM = 0.79) subgroups. Differences between subgroups were found only for competition level (P < 0.001) in relation to SAM (P = 0.001) and CAM (P < 0.001). For SAM, the highest and lowest values emerged for Federation (national, 5.1 ± 0.5; international, 5.4 ± 0.5) and State (national, 4.5 ± 0.9; international, 4.8 ± 0.7). The opposite picture emerged for CAM (Federation: national, 3.3 ± 0.7; international, 3.5 ± 0.9; State: national, 5.0 ± 0.8; international, 5.0 ± 0.9). Therefore, despite SAMSAQ-EU demonstrated to be a useful tool, results showed that European student-athletes' motivation for dual career has to be specifically investigated according to social contexts.